Dendritic cells in inflammatory angiogenesis and lymphangiogenesis. (August 2018) - Bosisio, Daniela; Ronca, Roberto; Salvi, Valentina; Presta, Marco; Sozzani, Silvano
Highlights: cDCs play a crucial role in reactive lymph nodes during inflammatory angiogenesis. This action largely depends on the secretion of VEGF-A. cDCs influence lymphangiogenesis also via the production of VEGF-C. cDCs secrete a plethora of other direct and indirect angiogenic factors. The role of pDCs and of cDC subsets remains to be elucidated. Abstract : Lymph node (LN) expansion during inflammation is essential to establish immune responses and relies on the development of blood and lymph vessels. Human dendritic cells (DCs), subdivided into two main subsets, namely conventional DCs (cDCs) and plasmacytoid DCs (pDCs), are professional antigen presenting cells endowed with the capability to produce soluble mediators regulating inflammation and tissue repair. cDCs support angiogenesis in secondary LNs both directly and indirectly through the secretion of vascular endothelial growth factor-A (VEGF)-A and VEGF-C and the production of several other mediators endowed with angiogenic properties. Finally, cDCs can affect neovascular formation via a transdifferentiation process. At variance with cDCs, the angiogenic properties of pDCs still remain poorly explored.